Mechanisms of resveratrol-induced changes in [Ca2+]i and cell viability in PC3 human prostate cancer cells. (October 2013) - Chang, Hong-Tai; Chou, Chiang-Ting; Chen, I-Li; Liang, Wei-Zhe; Kuo, Daih-Huang; Huang, Jong-Khing; Shieh, Pochuen; Jan, Chung-Ren
Abstract Resveratrol is a natural compound that affects cellular Ca2+ homeostasis and viability in different cells. This study examined the effect of resveratrol on cytosolic free Ca2+ concentrations ([Ca2+]i) and viability in PC3 human prostate cancer cells. The Ca2+-sensitive fluorescent dye fura-2 was used to measure [Ca2+]i and WST-1 was used to measure viability. Resveratrol-evoked [Ca2+]i rises concentration-dependently. The response was reduced by removing extracellular Ca2+. Resveratrol-evoked Ca2+ entry was not inhibited by nifedipine, econazole, SKF96365 and the protein kinase C inhibitor GF109203X, but was nearly abolished by the protein kinase C activator phorbol 12-myristate 13 acetate. In Ca2+-free medium, treatment with the endoplasmic reticulum Ca2+ pump inhibitor 2, 5-di-tert-butylhydroquinone decreased resveratrol-evoked rise in [Ca2+]i. Conversely, treatment with resveratrol inhibited BHQ-evoked rise in [Ca2+]i. Inhibition of phospholipase C with U73122 did not alter resveratrol-evoked rise in [Ca2+]i. Previous studies showed that resveratrol between 10 and 100 µM induced cell death in various cancer cell types including PC3 cells. However, in this study, resveratrol (1–10 μM) increased cell viability, which was abolished by chelating cytosolic Ca2+ with 1, 2-bis(2-aminophenoxy)ethane-N, N, N′, N′-tetra-acetic acid-acetoxymethyl ester (BAPTA/AM). Therefore, it is suggested that in PC3 cells, resveratrol had a dual effect on viability: at low concentrations (1–10 µM) it induced proliferation, whereas at higher concentrations it caused cell death. Collectively, our data suggest that in PC3 cells, resveratrol-induced rise in [Ca2+]i by evoking phospholipase C-independent Ca2+ release from the endoplasmic reticulum and Ca2+ entry, via protein kinase C-regulated mechanisms. Resveratrol at 1–10 µM also caused Ca2+-dependent cell proliferation.